Antiviral Activity of Myticin C Peptide from Mussel: an Ancient Defense against Herpesviruses - Novoa, Beatriz (J Virol, 2016)
Little is known about the antiviral response in mollusks. As in other invertebrates, the interferon signaling pathways have not been identified, and in fact, there is a debate about whether invertebrates possess antiviral immunity similar to that of vertebrates. In marine bivalves, due to their filtering activity, interaction with putative pathogens, including viruses, is very high, suggesting that they should have mechanisms to address these infections. In this study, we confirmed that constitutively expressed molecules in naive mussels confer resistance in oysters to ostreid herpesvirus 1 (OsHV-1) when oyster hemocytes are incubated with mussel hemolymph. Using a proteomic approach, myticin C peptides were identified in both mussel hemolymph and hemocytes. Myticins, antimicrobial peptides that have been previously characterized, were constitutively expressed in a fraction of mussel hemocytes and showed antiviral activity against OsHV-1, suggesting that these molecules could be responsible for the antiviral activity of mussel hemolymph. For the first time, a molecule from a bivalve has shown antiviral activity against a virus affecting mollusks. Moreover, myticin C peptides showed antiviral activity against human herpes simplex viruses 1 (HSV-1) and 2 (HSV-2). In summary, our work sheds light on the invertebrate antiviral immune response with the identification of a molecule with potential biotechnological applications. IMPORTANCE Several bioactive molecules that have potential pharmaceutical or industrial applications have been identified and isolated from marine invertebrates. Myticin C, an antimicrobial peptide from the Mediterranean mussel (Mytilus galloprovincialis) that was identified by proteomic techniques in both mussel hemolymph and hemocytes, showed potential as an antiviral agent against ostreid herpesvirus 1 (OsHV-1), which represents a major threat to the oyster-farming sector. Both hemolymph from mussels and a myticin C peptide inhibited OsHV-1 replication in oyster hemocytes. Additionally, a modified peptide derived from myticin C or the nanoencapsulated normal peptide also showed antiviral activity against the human herpesviruses HSV-1 and HSV-2. Therefore, myticin C is an example of the biotechnological and therapeutic potential of mollusks.